2019
DOI: 10.1108/jes-03-2018-0105
|View full text |Cite
|
Sign up to set email alerts
|

The effect of infrastructure and taxation on economic growth: new empirical assessment

Abstract: Purpose The purpose of this paper is to contribute to the empirical literature that analyzes the effect of the core infrastructure (telecommunication, electricity and transportation) and indirect taxation on economic growth. Design/methodology/approach The authors present empirical evidence through panel data analysis based on a comprehensive sample of countries (96) over a long period of time (1976 to 2014). Findings The findings confirm the assumption that the core of infrastructure is essential to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Furthermore, Dunning (1988) found that educated and skilled labor attracts FDI inflows. Dasgupta, Mody, and Sinha (1996) concluded that local skilled labor and high human resources capabilities attract FDI inflows (Noorbakhsh, Paloni, & Youssef, 2001). Dutta, Dutta, and Karmakar (2017) found that human capital significantly attracts FDI to host countries.…”
Section: Results Of Model 4 (Fdi)mentioning
confidence: 99%
“…Furthermore, Dunning (1988) found that educated and skilled labor attracts FDI inflows. Dasgupta, Mody, and Sinha (1996) concluded that local skilled labor and high human resources capabilities attract FDI inflows (Noorbakhsh, Paloni, & Youssef, 2001). Dutta, Dutta, and Karmakar (2017) found that human capital significantly attracts FDI to host countries.…”
Section: Results Of Model 4 (Fdi)mentioning
confidence: 99%
“…A tax policy that alleviates poverty improves economic growth in most instances (Biswas et al, 2017). Economic growth is closely associated with the broadened tax base (Bird, 2014), thus tax reform is among the mechanical tools that serve to both increase government revenue and encourage a country's economic development (Anojan, 2014; Laurindo de Almeida & Ferreira de Mendonça, 2019; Shrivastava et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, no aid is to be granted to most developing countries if no effort has been made by such countries for tax reform, whereby, tax effort is used as a benchmark for the provision of aid and grants from world financial institutions and other donor countries (Fjeldstad & Rakner, 2003; OECD, 2014; Laurindo de Almeida & Ferreira de Mendonça, 2019). Through the reviewed literatures, it was revealed that most of the current economic discussions from the country level to the international level are about human development, and taxation seems to be the main financing tool for human development (Balsera et al, 2017; Etim et al, 2020; OECD, 2014; Reeves et al, 2015; Tuan et al, 2012; United Nations, 2007; UNDP, 2013; United Nations Economic Commission for Africa, 2019).…”
Section: Identification Of the Problemmentioning
confidence: 99%
“…Infrastructure, according to previous research, boosts economic activity since it is employed in practically every manufacturing process, including telecommunications, energy, water, and transportation [7,9]. Thus, infrastructure, which is an input into all manufacturing processes, has a beneficial effect on economic growth, productivity, and growth rates [10]. Hence, infrastructure has three effects on economic development: it increases production and employment; it increases human capital and improves people's social lives by providing better facilities such as education and health; and, finally, it improves financial facilities such as monetary transactions, loans, and other services [4,11,12,13].…”
Section: Introductionmentioning
confidence: 99%